Hard and soft climate-smart investments in aquaculture in Bangladesh: Conditioning factors and decision space - Amjath Babu, Tharayil Shereef; Hossain, Peerzadi Rumana; Anee, Sanzida Akhter; Mohammed, Essam Yassin; Krupnik, Timothy Joseph (Elsevier, 2025)
Climate change and its' associated weather variabilities and extremes are posing significant risks to aquaculture productivity, particularly in the coastal regions of Bangladesh. Concurrently, the increasing population and shifting consumption patterns are driving higher demand for aquacultural products. This study investigates the impact of floods, heavy rainfall, tidal surges, high temperatures, droughts, erratic rainfall, and water quality parameters (Dissolved Oxygen, ammonia, pH) on investments in "hard" assets, such as specific fish-farm equipment (aquaculture nets, fish cages, thermometers, irrigation pumps), to enhance climate resilience. Additionally, the study explores "soft" investments in information services that provide advanced forecasts on monsoon onset, heavy rainfall, dry spells, high temperature and cold spells. The results indicate that the level of investment in climate-smart aquaculture is currently influenced by climate stresses, investment capacity (farm size, family size), aquaculture system characteristics (pond size and depth, type of fish, aggregate yields), and market-related factors (proximity to roads and markets). In the context of climate-informed decision-making, forecast-based advisory services can facilitate the transition to climate-smart aquaculture. However, the benefits of the information services are often linked to substantial investments in hard infrastructure that ensure the effective utilization of climate information and advisory services. This absence of accessible climate information services and the capacity to invest in climate smart equipment that makes the information actionable, hinder the transition to climate smart aquaculture by smallholder farmers and hence threaten their livelihood and nutritional security.